PRIMEIRO REGISTRO DOCUMENTADO DO CAMARÃO-TIGRE-GIGANTE, Penaeus monodon (Fabricius, 1798), NO LITORAL DO CEARÁ, NORDESTE DO BRASIL - Dayse de Vasconcelos Silva, Grasielle; Adayllana de Vasconcelos Silva, Giselle; Camargo Maia, Rafaela (Arquivos de Ciências do Mar, 2023)
This note records the first occurrence of the giant-tiger-shrimp, Penaeus monodon, in the coast of Ceará and compiles the current published reports of the species in Brazil. Keywords: coastal area, exotic species, Penaeidae.